The health care handbook : a clear and concise guide to the United States health care system - Askin, Elisabeth; Moore, Nathan ;Peck, William ([St. Louis] : Washington University in St. Louis, 2012)
The American health care system is vast, complex and confusing. Books about it shouldn't be. This book is your one-stop guide to the people, organizations and industries that make up the U.S. health care system and the major issues the system faces today. The book is the work of two medical students at Washington University, Elisabeth Askin and Nathan Moore. When Elisabeth and Nathan worked to educate themselves about the American health care system they couldn't find a source that was comprehensive, understandable and non-biased - so they decided to write it themselves. It's rigorously researched and scrupulously unbiased yet written in a conversational and humorous tone that's a pleasure to read and illuminates the convoluted health care system and its many components. The book is essential reading for health professionals, health professions students, and anyone who interacts with the U.S. health care system.
Health care systems and delivery -- Health care providers -- Insurance and economics -- Research, pharmaceuticals, and medical devices -- Policy and reform.
Includes bibliographical references (pages 228-231) and index.
Keywords: MEDICAL CARE -- UNITED STATES